Gonad development and reproductive cycle of the green tiger prawn Penaeus semisulcatus (de Haan,1844) from Pilar and Capiz Bays, Northern Panay - Villarta, Karen Agnes
The gonad development and reproductive cycles of both sesx of the green tiger prawn Penaeus semisulcatus (de Haan, 1844), from Pilar and Capiz Bayys, northern Panay, central Phils were studied over a one-year period from January to December 2002. Numbers of female and male specimens sampled per month ranged from 14 to 30 and 2 to 28, respectively. Sizes ranged from 112 to 245 mm in total length for females, and 104 to 187 m for males. The smallest size observed to have a ripe gonad was 123 mm for males, and 145 mm for females. However, partially spawned individuals were observed at much smaller sizes for both male and female at total lengths of 104 mm and 143 mm, respectively. These results suggest that the minimum size at sexual maturity is <123 mm for males, and <145 mm for females. Gonad maturation was monitored by menas of the gonado-somatic index (GSI; while maturation stages were based on histology (immature, developing, ripe, partially spawned, redeveloping). GSI values for the male shrimps did not show a clear trend throughout the year, although peaks were observed during the months of May, August, October and Decemebr. GSI of females on the other hand, exhibited a major peak from June to September and a minor peak in January. Section of the ovaires from mature female P. semisulcatus showed oocytes in the cortical rod stage predominate in shrimps of size range 100-199.99 and 200-299.99 um. Further, no significant variation of oocyte sizes were observed throughout the reproductive cylce. Altogether , these results suggest the occurence of mature male and female P. semisulcatus almost a year round, indicating that this species is a continuous breeder, and is therefore a potential species for shrimp aquaculture in the PHilippines.